Process optimization approach in fine pitch Cu wire bonding - Wong B.K.; Yong C.C.; Eu P.L.; Yap B.K. (2023)
With SiO2 dielectric under aluminum pads, a 60 m bond pad pitch with 52 um bond pad opening Cu wire bonding process was developed in PBGA Hip 7 PGE wafer technology. The critical factors (wire type, capillary, and bonding parameter) and critical responses (bonded ball diameter, bonded ball height, wire pull, ball shear and number of metal lift/peeling and ball lift after wire pull) are affecting bonding quality. Design of experiment and response of surface were used to optimize the bonding parameters. The wire pull and ball shear test at three thermal aging read points were studied. 2011 IEEE.